Navigating the Complexities of Qualitative Research in Built Environmental Studies: Methodologies, Philosophies, and Credibility - Paudel, Ram (International Journal of Applied and Scientific Research, 2023)
Qualitative research is renowned for its ability to investigate intricate scenarios and produce in-depth insights, and it is especially well-suited when human subjects are involved. Consequently, it has experienced a surge in popularity within the field of built environmental research. Researchers may encounter inherent complexities when employing qualitative research techniques. In response to these challenges, this working paper seeks to comprehensively examine the matter by delving into relevant issues, including the distinctive characteristics of research, research methodologies encompassing research philosophies, the rationale behind research decisions, and data treatment at the fundamental level. The final segment of this discourse revisits the critical issue of ensuring the credibility of research findings. The objective of this working paper's discussion is to serve as a source of inspiration for students and researchers considering the adoption of qualitative methods in their research endeavors or who are currently utilizing them. It is intended to equip them with a robust understanding of these pertinent aspects, enabling them to leverage the insights presented here for the successful execution of their research projects.